Building Entrepreneurial Values in Inclusive Education in Early Childhood Schools - Fitria, Adilah Wina; Romansyah, Romansyah; Wahira, Wahira (PT ARRUS Intelektual Indonesia, 2025)
Early childhood education (ECED) plays an important role in forming the foundation of children's character and social skills. One of the challenges faced by early childhood education is the lack of integration of entrepreneurial values in the curriculum. In fact, educational entrepreneurship can be an effective approach to creating an inclusive learning environment, encouraging creativity and developing much-needed social skills in the future. Entrepreneurship is not just about business, but involves attitudes, values and the ability to innovate and create something that benefits society. In the context of inclusive education in ECD, the application of entrepreneurship can help children to think creatively, solve problems and work together, which is highly relevant for their social and emotional development. This article examines how educational entrepreneurship can be applied in inclusive ECD classrooms and the role of teachers in creating spaces that support diversity and holistic child development. Through an entrepreneurial approach, it is hoped that more inclusive learning opportunities can be created and have a positive impact on children's life skills, equipping them with independence, confidence and the ability to face future challenges.